THE ROLE OF THE PORT BUSINESS ENTITY (BUP) PT. PELINDO III IN THE CONTEXT OF REALIZING GREEN & SMART PORT OPERATIONS AT TERMINAL TELUK LAMONG SURABAYA - Muhammad Dahri; Prima Yudha Yudianto; Imam Sutrisno (Jurnal Scientia, 2023)
PT. Teluk Lamong Terminal is a subsidiary of Pelindo III. Terminal operator that prioritizes services with high-tech facilities with the concept of “The first green port in Indonesia. The role and steps taken by BUP PT. Teluk Lamong Terminal in realizing a green port includes: (a) Improving the quality of cleanliness, port environment, (b) Improving service facilities, security, order and public safety. (c) Increasing institutional capacity and human resources for environmental management in the port area. (d) Implementing Regulations and Technical Guidelines that support the management of the port environment for the realization of legal certainty. (e) Increasing the active role of stakeholders in realizing environmentally friendly ports. The role of BUP PT. Teluk Lamong Terminal in implementing Smart Port includes: The implementation of the interconnection of the entire port logistics chain includes (a) an intelligent information system consisting of ; (b) data center (c) cyber security.